Influence of strength and power training on the rate of force development, peak force and functional mobility in elderly people with Parkinson's disease: a randomized controlled trial - Amaral Felipe, Késia Maísa do [UNESP]; Yamada, Patrícia de Aguiar [UNESP]; Meneghetti, Tamires; Faganello-Navega, Flávia Roberta [UNESP] (Frontiers, 2025)
Objective: To analyze the influence of lower limb muscle strength and muscle power training on rate of force development (RFD) and peak force (PF) in elderly people with Parkinson's disease (PD), as well as the effect of these training sessions influence on the functional mobility (FM) of this population. Methods: This was a randomized controlled clinical trial and registered on the virtual platform for registration of experimental and non-experimental studies “Registro Brasileiro de Ensaios Clínicos (ReBEC)”. Thirty four elderly people of both genders without and with PD were divided into four groups: strength training control (GSC, n = 8); potency training control (GPC), n = 9; subjects with PD submitted to strength training (GSPD, n = 8); subjects with PD submitted to potency training (GPPD, n = 9). GSC and GPC consisted of with no history of neurological diseases. PF and RFD in the first 50 and 200 milliseconds (ms) were determined. FM was also assessed using the following tests: gait speed test (GS), Timed Up and Go (TUG), Short Physical Performance Battery (SPPB), Unified Parkinson's Disease Rating Scale (UPDRS); parallel feet on a force platform. Next, the participants underwent lower limbs muscle strength or muscle power training for eight consecutive weeks twice a week and were then re-evaluated. Results: The repeated measures ANOVA test showed a significant difference for PF, RFD and FM regardless of training type. Conclusion: The proposed muscle strength and muscle power training protocols influenced the increase in RFD, PF and FM of all participants; however, the increase in RFD in the first 200 ms was more pronounced in the groups submitted to power training and the increase in PF was more pronounced in the groups submitted to strength training.
Keywords: elderly people; lower limb; muscle power; muscle strength; Parkinson's disease